THE METABOLISM OF AMINO ACIDS - Gavran, Mirna; Gantner, Vesna (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The building blocks of proteins, amino acids, play a crucial role in both animal and human metabolism and structure. In light of the fact that amino acids are crucial to life, the goal of this review was to analyze their metabolism. It is the liver that has the primary role in the metabolism of amino acids in humans and animals. It is possible to divide amino acids into essential and non-essential ones. Cell membranes in various tissues are the major route through which amino acids travel to the blood, primarily via cotransport systems dependent upon Na+. In most land animals, the ammonium ion is converted to urea. Excess NH4+ is converted into urea. The process by which this takes place is called the urea cycle.  During the process, glutamate dehydrogenase generates free NH4+ previously transferred to α-ketoglutarate by transaminases. Fumarate, another product, links the urea cycle to the TCA cycle. The two input nitrogen atoms exit the cycle as urea, which the liver releases into the blood for disposal in the urine via the kidneys. Ammonia could be very toxic to the cells and tissues of all living beings. Therefore, knowing amino acid metabolism is crucial for human and animal nutrition to prevent the prevalence of numerous disorders or diseases.